Low temperature alkaline activation of weathered fly ash: Influence of mineral admixtures on early age performance. (1st July 2015) - Messina, Francesco; Ferone, Claudio; Colangelo, Francesco; Cioffi, Raffaele
Highlights: Alkaline activation is an innovative recovery technology for weathered fly ash. Several mineral admixtures (slag, silica fume, metakaolin) are considered. Technological properties (workability, strength, shrinkage, etc.) are quantified. An efficiency index is calculated to compare synthetically the binary mixtures. Blast furnace slag and metakaolin reveal to be the most effective admixtures. Abstract: In the field of alkali activated materials, weathered fly ash represents a scarcely explored edge, since most of the studies related to alkali activated fly ash use qualified/highly reactive samples. In this work, early-age behavior of several binary alkali activated binders was assessed in terms of workability, chemical shrinkage, strength development and ultrasonic pulse velocity. The mineral admixtures in the binary systems were blast furnace slag, silica fume and metakaolin. Curing temperature was fixed at 20 °C, in opposition to most literature studies that focused on more energy-intensive curing conditions. An efficiency index was defined and calculated in order to synthesize all the results and compare the binders. Silica fume addition did not determine performance improvement even at significant mass percentages (up to 15%). Metakaolin improved significantly the mechanical performance but reduced excessively the paste flowability. Blast furnace slag revealed to be the most effective secondary component, since this system was able to develop a highly promising mechanical performance and exhibit a satisfactory flowability and low early age shrinkage.